Wings of fire. Book one, The dragonet prophecy : the graphic novel - Sutherland, Tui, 1978-; Deutsch, Barry (Graphix, an imprint of Scholastic, 2018)
Determined to end a generations-long war among the seven dragon tribes, a secret movement called the Talons of Peace draws on a prophecy that calls for a great sacrifice, compelling five appointed dragonets to fulfill a painful destiny against their will.